If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1 + 8z + -7x + z = 0 Reorder the terms: -1 + 9x + -7x + 8z + z = 0 Combine like terms: 9x + -7x = 2x -1 + 2x + 8z + z = 0 Combine like terms: 8z + z = 9z -1 + 2x + 9z = 0 Solving -1 + 2x + 9z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 2x + 1 + 9z = 0 + 1 Reorder the terms: -1 + 1 + 2x + 9z = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2x + 9z = 0 + 1 2x + 9z = 0 + 1 Combine like terms: 0 + 1 = 1 2x + 9z = 1 Add '-9z' to each side of the equation. 2x + 9z + -9z = 1 + -9z Combine like terms: 9z + -9z = 0 2x + 0 = 1 + -9z 2x = 1 + -9z Divide each side by '2'. x = 0.5 + -4.5z Simplifying x = 0.5 + -4.5z
| 2x^2+17xy+8y^2= | | 8(2x+1)=11x+53+5x | | -x+9=x-21 | | x+9=x-21 | | x/9=40/5 | | 2x+1=x^2-14x+49 | | 5x+46=x^2+16x+64 | | 36=2x*3y | | x^2+4x+4+14x+28+45=0 | | 7(x-2)=-6+9x | | 3x^2-7-6=0 | | x+12=3x+20 | | -5y+8/3=5/4+4y+2 | | 6y-7=29 | | z/2-11/7-z/3=-3z/5 | | 7(2d-9)= | | 8z-5/3=z-7/5-9z/4 | | 2x^3-5x^2-11x=0 | | 54-9y+y=6 | | 11y+6/3-8y/5=2y+4/8 | | 0=-2x+9 | | 18=-10d+15 | | 12x/5+2/7=2x/3+3/5-4x | | 5x+2/3=5x/3 | | 1/2+9z/4=-7/5 | | -2x/3+1/2=-5/3 | | 1+(8y-6)=-(4y+8)+8 | | 5x/4+3=0 | | -3/2-2y=0 | | √x²+64=17 | | 6-10c=58 | | (-5z+1)(16z+2)=2+(-2z+4)(40z+4)+7z |